Diversity and effects of competitive Trichoderma species in Ganoderma lucidum–cultivated soils - Wang, Yongjun; Zeng, Linzhou; Wu, Jiayi; Jiang, Hong; Mei, Li (Frontiers in Microbiology, 2022)
Ganoderma lucidum (GL) is a well-known medicinal mushroom that has been extensively cultivated. Abundant Trichoderma colonies have been found on the casing soil surface, posing cultivation obstacles for GL. In this study, the diversity and effects of Trichoderma from GL-cultivated soils were investigated. Over 700 Trichoderma isolates were collected from two trails in Longquan Country, southeast China. Eight Trichoderma species, including T. atrioviride, T. guizhouense, T. hamatum, T. harzianum, T. koningiopsis, T. pleuroticola, T. spirale, and T. virens, were identified based on the combination alignment of tef-1α and rpb2 sequences. The number of Trichoderma colonies increased dramatically during GL cultivation, with an increase of 9.2-fold in the Lanju trail. T. virens accounted for the most colonies (33.33% and 32.50% in Lanju and Chengbei, respectively) at the end of GL cultivation. The Trichoderma species growth varied but was satisfactory under different temperature or pH conditions. Moreover, Trichoderma species showed different adverse effects on GL growth. The non-volatile metabolites from T. virens and volatile metabolites from T. atroviride displayed the strongest antagonistic activity. Furthermore, the volatile 6-pentyl-2H-pyran-2-one (6-PP) showed a significant inhibitory effect on GL growth with an 8.79 μL mL−1 headspace of 50% effective concentration. The different Trichoderma spp. Produced different amounts of 6-PP. The most efficient 6-PP producer was T. atroviride. To the best of our knowledge, this study is the first to demonstrate the abundance of competitive Trichoderma species associated with GL cultivation.